2012
DOI: 10.1128/jcm.00387-12
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a PCR Assay for Tracking the Emergence and Dissemination of Haitian Variant ctxB in Vibrio cholerae O1 Strains Isolated from Kolkata, India

Abstract: A PCR-based assay was developed to discriminate the classical, El Tor, and Haitian types of ctxB alleles. Our retrospective study using this newly developed PCR showed that Haitian ctxB first appeared in Kolkata C holera still continues to be an important cause of human infection, especially in developing countries that lack access to safe drinking water and proper sanitation. The recent devastating cholera outbreak in Haiti (13), for the first time in almost a century, placed this ancient disease at the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
104
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 15 publications
10
104
0
1
Order By: Relevance
“…This emergence and spread of altered-ET in Asia and Africa had huge epidemiological implications, as ET carrying ctxB1 was associated with more severe disease (Siddique et al, 2010). Further change in the CTX prophage gene (histidine to asparagine at the twentieth position of CtxB) resulting in substitution of ctxB1 with ctxB7 was reported in 2006 from India (Naha et al, 2012). A similar change from ctxB1 to ctxB7 also occurred in V. cholerae O1 responsible for endemic cholera in Dhaka, Bangladesh, but not before 2008 (Rashed et al, 2012), suggesting a possible transmission of V. cholerae carrying the ctxB7 from neighbouring India, which was detected later in Africa and Haiti (Hasan et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This emergence and spread of altered-ET in Asia and Africa had huge epidemiological implications, as ET carrying ctxB1 was associated with more severe disease (Siddique et al, 2010). Further change in the CTX prophage gene (histidine to asparagine at the twentieth position of CtxB) resulting in substitution of ctxB1 with ctxB7 was reported in 2006 from India (Naha et al, 2012). A similar change from ctxB1 to ctxB7 also occurred in V. cholerae O1 responsible for endemic cholera in Dhaka, Bangladesh, but not before 2008 (Rashed et al, 2012), suggesting a possible transmission of V. cholerae carrying the ctxB7 from neighbouring India, which was detected later in Africa and Haiti (Hasan et al, 2012).…”
mentioning
confidence: 99%
“…In this study, a significant correlation was observed between the clinical and environmental strains carrying either ctxB1 or ctxB7 (Spearman's correlation coefficient50.973; P50.005). Although the epidemiological significance of the change from ctxB7 to ctxB1, as observed in Bangladesh during 2013-2014, is not well understood, the competition of the ctxB genotypes and their temporal shift in V. cholerae responsible for cholera at different ecological settings provide in situ evidence of CTX prophage-mediated evolution of the bacterium (Naha et al, 2012;Rashed et al, 2013;Alam et al, 2014). The limitation of the present study is that the SNPs of ctxB were monitored, not the genome-wide SNPs that have been proposed to drive positive selection of V. cholerae in Haiti (Azarian et al, 2014); and so, the synergistic role in the observed genotypic shift of SNPs elsewhere in the V. cholerae genome cannot be ruled out.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DMAMA-PCR was recently developed to discriminate the CL (ctxB genotype 1), ET (ctxB gneotype 3) and Haitian types (ctxB genotype 7) of ctxB alleles by focusing on nucleotide positions 58 and 203 of the ctxB gene (Naha et al, 2012). DMAMA-PCR was performed in this study to detect the ctxB genotype using the primers and conditions described elsewhere (Naha et al, 2012). V. cholerae O1 strains O395 (CL), N16961 (ET) and 2010EL-1786 (Haiti variant, genotype 7) were used as control strains for DMAMA-PCR analysis.…”
Section: Double Mismatch Amplification Mutation Assay (Dmama)-pcrmentioning
confidence: 99%
“…A recent study in India reported that a new CT variant of V. cholerae O1 ET with an amino acid substitution at position 20 caused a large cholera outbreak in Orissa, Eastern India (Kumar et al, 2009). Subsequently, the same CT variant was found to have been associated with cholera in Kolkata, India, since 2006 (Naha et al, 2012). Considering these recent changes, the current study was undertaken in order to understand the phenotypic and genetic traits of contemporary V. cholerae causing endemic cholera in Dhaka, Bangladesh.…”
Section: Introductionmentioning
confidence: 99%